Abortion saves a beating heart - Schultz, David Andrew (Medicine, law & society, 2024)
The 2022 US Supreme Court’s Dobbs v Jacksons Women Health Organization decision placed abortion rights back into the center of US and global politics. At a time when across the world abortion rights were continuing to expand, the US appeared to be retrenching on it. Dobbs renewed the debate about abortion as a political or human right. But often overlooked in the discussion of the topic is how access to abortion is a medical and health issue. This Article examines abortion as a health care issue. It constructs a cross-national aggregate database looking at the relationship between more permissive abortion laws and the promotion of health. It finds that more permissive abortion laws nationally are correlated with better health care outcomes for women, pregnant mothers, and newborns. It also finds that more permissive abortion laws are associated with democracies and the percentage of women in national legislatures.
Keywords: abortion; cross-national; democracy; health outcomes; reproductive rights